Patient and public involvement in care home research: Reflections on the how and why of involving patient and public involvement partners in qualitative data analysis and interpretation - Rachel Stocker; Katie Brittain; Karen Spilsbury; Barbara Hanratty (Wiley, 2021)
Abstract Background There is limited evidence for the impact of involving patients and the public (PPI) in health research. Descriptions of the PPI process are seldom included in publications, particularly data analysis, yet an understanding of processes and impacts of PPI is essential if its contribution to research is to be evaluated. Objective To describe the 'how' of PPI in qualitative data analysis and critically reflect on potential impact. Methods We focus on the development and critical reflection of our step‐by‐step approach to collaborative qualitative data analysis (through a series of analysis workshops) in a specific care home study, and our long‐term engagement model with patients and the public (termed PPI partners). Results An open access PPI group, with multiple events over time, sustained broad interest in care home research. Recordings of interview clips, role‐play of interview excerpts and written theme summaries were used in workshops to facilitate PPI partner engagement with data analysis in a specific study. PPI resulted in changes to data interpretation and was perceived to make the research process accessible. We reflect on the challenge of judging the benefits of PPI and presenting PPI in research publications for critical commentary. Conclusions Patient and public involvement partners who are actively engaged with data analysis can positively influence research studies. However, guidance for researchers is needed on approaches to PPI, including appropriate levels and methods for evaluation. Without more systematic approaches, we argue that it is impossible to know whether PPI represents good use of resources and is generating a real impact.